2012
DOI: 10.1002/agr.21289
|View full text |Cite|
|
Sign up to set email alerts
|

On the Frequency, Depth, and Duration of Sales at High–Low Pricing Supermarkets

Abstract: This study examines the phenomenon of advertised sales, or price discounts, at major high-low pricing (HLP) supermarkets in the United States. The authors measure and document price variability and movement using a unique and rich dataset on prices and sales drawn directly from supermarkets. Several of their key findings pertain directly to an influential study by Hosken and Reiffen (2004) on retail price variation. However, the authors' estimate of price rigidity is lower than Hosken and Reiffen's while their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Another key difference is the length of these two types of price changes. Promotions are temporary and shelf price changes are much longer in duration (Hosken and Reiffen, ; Volpe and Li, ). Promotions, therefore, are of interest to researchers studying short‐run demand elasticity, retail category management, and the economics of the wholesaler–retailer relationship.…”
Section: How and Why Retail Food Prices Changementioning
confidence: 99%
“…Another key difference is the length of these two types of price changes. Promotions are temporary and shelf price changes are much longer in duration (Hosken and Reiffen, ; Volpe and Li, ). Promotions, therefore, are of interest to researchers studying short‐run demand elasticity, retail category management, and the economics of the wholesaler–retailer relationship.…”
Section: How and Why Retail Food Prices Changementioning
confidence: 99%
“…Coined the “theoretical lynchpin” of price rigidity by Blinder et al (1998), little consistent evidence has been produced to the relevance of menu costs in retailer pricing strategies (Dutta et al, 2002; Knotek, 2019). In contrast, several studies provide empirical evidence in favor of retailer strategies as the source of fluctuations in pricing rather than input or menu costs (Kashyap, 1995; Volpe & Li, 2012). Owen and Trzepacz (2002) concluded that “pricing strategy,” such as “everyday low price” (EDLP) or “high‐low price” (Hi‐Lo) is the most important determinant of the probability of a “price change” (p. 347).…”
Section: Literature and Evidencementioning
confidence: 99%
“…Anders and Beye (2015) examined this phenomenon and found evidence that this is explained in part by social consumption, in a study that incorporated tiered PLs. Volpe and Li (2012), who examined multiple product supermarket categories, found that overall price rigidity was higher for PLs and that PLs were subject to more promotional activity. Hong and Li (2017) found evidence that vertical structure is important for explaining passthrough and found the highest rates of passthrough for retailer owned PLs and the lowest rates for NBs.…”
Section: Literature and Evidencementioning
confidence: 99%
“…Although some retailers do engage in localized pricing (charging different prices at stores using the same retail banner within the same broad geographic market), it is unclear how important this within market retailer price variation is empirically. Volpe and Li (), for instance, found that two large chain retailers charged essentially the same prices at their outlets in many locations throughout the Los Angeles metropolitan area.…”
Section: Market and Price Constructionmentioning
confidence: 99%